Porównanie metod określania wydatku energetycznego na przykładzie leśnictwa - Grzywiński, Witold; Bembenek, Mariusz; Mederski, Piotr (Leśne Prace Badawcze, 2014)
In this paper the values of energy expenditure obtained with estimative methods (tables of energy expenditure, Lehmann’s method) were compared to the data obtained with a method based on pulmonary ventilation measurements. Thereby, the usefulness of estimative methods for determining energy expenditure on work stations in forestry was tested. We compared energy expenditures for 30 forestry work stations within which 59 different activities were distinguished. For each activity the energy expenditure was determined utilizing the three following methods: pulmonary ventilation measurement, tables of energy expenditure and Lehmann’s method. The percentage error in energy expenditure for particular activities determined with tables ranged from -44.47% to 42.31%. The highest representation of error value (52.8%) varied between 19.9% and 5.0%. The error in energy expenditure estimation determined with Lehmann’s method is characterized by a smaller variability ranging from -31.35% to 34.13%. The highest density of error values was found in the range from -4.9% to 10.0%, which comprises 44.1% of the results. To conclude, the use of tables resulted in an underestimation of the energy expenditure value for 64.1% of activities, whereas the use of Lehmann’s method resulted in an underestimation in 49.1% of the cases.